Biologic treatments for sports injuries II think tank - Current concepts, future research, and barriers to advancement, Part 1 - LaPrade, R. F.; Geeslin, A. G.; Murray, I. R.; Musahl, V.; Zlotnicki, J. P.; Petrigliano, F.; Mann, B. J. (The American Journal of Sports Medicine, 2016)
Biologic therapies, including stem cells, platelet-rich plasma, growth factors, and other biologically active adjuncts, have recently received increased attention in the basic science and clinical literature. At the 2015 AOSSM Biologics II Think Tank held in Colorado Springs, Colorado, a group of orthopaedic surgeons, basic scientists, veterinarians, and other investigators gathered to review the state of the science for biologics and barriers to implementation of biologics for the treatment of sports medicine injuries. This series of current concepts reviews reports the summary of the scientific presentations, roundtable discussions, and recommendations from this think tank.